The Role of MicroRNAs in Development and Function of Regulatory T Cells – Lessons for a Better Understanding of MicroRNA Biology - Kunze-Schumacher, Heike; Krueger, Andreas (Frontiers in Immunology, 2020)
MicroRNAs (miRNAs) have emerged as critical posttranscriptional regulators of the immune system, including function and development of regulatory T (Treg) cells. Although this critical role has been firmly demonstrated through genetic models, key mechanisms of miRNA function in vivo remain elusive. Here, we review the role of miRNAs in Treg cell development and function. In particular, we focus on the question what the study of miRNAs in this context reveals about miRNA biology in general, including context-dependent function and the role of individual targets vs. complex co-targeting networks. In addition, we highlight potential technical pitfalls and state-of-the-art approaches to improve the mechanistic understanding of miRNA biology in a physiological context.